Ternary-salt solid polymer electrolyte for high-rate and long-life lithium metal batteries. Issue 78 (12th September 2022) - Liu, Zhi Kang; Guan, Jun; Yang, Hai Xia; Sun, Peng Xiao; Li, Nian Wu; Yu, Le
Abstract : A ternary-salt solid polymer electrolyte consisting of LiPF6 -LiTFSI-LiFSI salts and poly(1, 3-dioxolane) was developed through an in situ polymerization for a stable Li metal anode. Abstract : A ternary-salt solid polymer electrolyte (TS-SPE) consisting of LiPF6 -LiTFSI-LiFSI salts and poly(1, 3-dioxolane) is created by in situ polymerization. The TS-SPE possesses high ionic conductivity, high Li + ion transference number, and stable SEI with low interfacial impedance, thereby realizing excellent rate performance and long-life stability in Li metal batteries.